Pulmonary Sound Design Using Max 9814 Sensor with Nextion View - Febrianti, Fani; Setioningsih, Endang Dian; Utomo, Bedjo; sumber, sumber (Jurusan Teknik Elektromedik, Politeknik Kesehatan Kemenkes Surabaya, Indonesia, 2023)
This study aims to develop a tool that can assist nurses in examining patients by displaying sounds and signals on a TFT LCD screen. This tool uses the MAX 9814 sound sensor, which converts sound into an electrical signal. This sensor will generate a voltage when the diaphragm inside it moves back and forth. To design this tool, researchers used a series of high pass filters and low pass filters with a cut-off frequency of 333 Hz - 714 kHz. During testing of this tool using the MAX 9814 sensor mounted on a stethoscope, the signal appears stable on the TFT LCD screen and sound can be played properly. However, if the placement of the stethoscope is not correct during the examination, this can also affect the signal and sound produced. This tool should not produce a clear and loud sound when checking, because if this happens, the inspection cannot be carried out optimally. This research also produces a signal shape that is almost similar to the signal on the phantom. It is important to note that the MAX 9814 can work optimally if it is not exposed to environmental noise. Therefore, if this equipment is used in a noisy environment, the signal and sound produced may be disturbed by environmental noise. This research was conducted with the aim of making it easier for doctors and nurses to carry out portable examinations, as well as to monitor signals and sounds easily.